2013
DOI: 10.1371/journal.pone.0058410
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Functional Analysis of Four Glutathione S-Transferases from the Migratory Locust, Locusta migratoria

Abstract: Glutathione S-transferases (GSTs) play an important role in detoxification of xenobiotics in both prokaryotic and eukaryotic cells. In this study, four GSTs (LmGSTd1, LmGSTs5, LmGSTt1, and LmGSTu1) representing different classes were identified from the migratory locust, Locusta migratoria. These four proteins were heterologously expressed in Escherichia coli as soluble fusion proteins, purified by Ni2+-nitrilotriacetic acid agarose column and biochemically characterized. LmGSTd1, LmGSTs5, and LmGSTu1 showed h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 55 publications
5
43
1
Order By: Relevance
“…Functional information regarding those clades is scarce. L. migratoria GSTu1 is expressed in Malpighian tubules and its downregulation using RNAi leads to a higher sensitivity to carbaryl and chlorpyrifos insecticides (Qin et al, 2013). In silkworm, BmGSTu2 is induced in a resistant strain and is able to conjugate glutathione to the organophosphate insecticide diazinion (Yamamoto and Yamada, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Functional information regarding those clades is scarce. L. migratoria GSTu1 is expressed in Malpighian tubules and its downregulation using RNAi leads to a higher sensitivity to carbaryl and chlorpyrifos insecticides (Qin et al, 2013). In silkworm, BmGSTu2 is induced in a resistant strain and is able to conjugate glutathione to the organophosphate insecticide diazinion (Yamamoto and Yamada, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Insect GSTs, particularly the delta and epsilon classes, are known to be involved in the metabolism of both plant defense compounds and insecticides, and have been identified as an important class of detoxification enzymes . In this study, we identified and characterized one delta class ( DcGSTd1 ) and two epsilon class ( DcGSTe1 and DcGSTe2 ) GST genes in D. citri .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, RNAi experiments in L. migratoria nymphs resulted in significant decreases in transcript levels of GSTs5 and GSTu1 [52]. Insecticide bioassays showed that dsRNA-injected nymphs become more susceptible to carbaryl, as indicated by increases in mortality by 28 and 12%, respectively, after GSTs5 and GSTu1 were silenced.…”
Section: Identifications Of Genes Involved In Insecticide Detoxificatmentioning
confidence: 90%